Collaborative Governance Dalam Pelaksanaan Program Kampung Iklim Di Kelurahan Palupi Kecamatan Tatanga Kota Palu - Ristamala; Mufti, Mohammad Irfan; Ferianto, Fiki (JPS: Journal of Publicness Studies, 2026)
This study aims to analyze the implementation of Collaborative governance in the Climate Village Program (ProKlim) in Palupi Village, Palu City. This program is a government initiative to enhance community resilience to climate change through adaptation and mitigation activities based on community participation. This research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation. The results show that the implementation of ProKlim in Palupi Village involves collaboration among local government, village authorities, program managers, and the community. Based on Ansell and Gash’s Collaborative governance framework, the initial conditions indicate relatively good relationships among stakeholders, although limitations in resources and coordination remain. In terms of institutional design, the program has followed existing regulations but lacks sufficient financial support. Facilitative leadership is reflected in the role of government as a facilitator that encourages community participation through assistance and direct involvement in activities. Meanwhile, the collaborative process demonstrates ongoing communication, trust-building, and shared understanding, although these aspects still need continuous improvement. Overall, the collaboration in implementing ProKlim in Palupi Village has been relatively effective and has contributed positively to environmental quality improvement and community participation. However, several challenges persist, including limited resources, suboptimal coordination, and uneven public understanding of the program. Therefore, strengthening coordination, improving resource capacity, and ensuring continuous government support are necessary to enhance the effectiveness and sustainability of the program.